Inactivated Rabies Virus Vectored MERS-Coronavirus Vaccine Induces Protective Immunity in Mice, Camels, and Alpacas - Chi, Hang; Wang, Yanqun; Li, Entao; Wang, Xiwen; Wang, Hualei; Jin, Hongli; Han, Qiuxue; Wang, Zhenshan; Wang, Xinyue; Zhu, Airu; Sun, Jing; Zhuang, Zhen; et al. (Frontiers in Immunology, 2022)
Middle East respiratory syndrome coronavirus (MERS-CoV) is an emergent coronavirus that has caused frequent zoonotic events through camel-to-human spillover. An effective camelid vaccination strategy is probably the best way to reduce human exposure risk. Here, we constructed and evaluated an inactivated rabies virus-vectored MERS-CoV vaccine in mice, camels, and alpacas. Potent antigen-specific antibody and CD8+ T-cell responses were generated in mice; moreover, the vaccination reduced viral replication and accelerated virus clearance in MERS-CoV-infected mice. Besides, protective antibody responses against both MERS-CoV and rabies virus were induced in camels and alpacas. Satisfyingly, the immune sera showed broad cross-neutralizing activity against the three main MERS-CoV clades. For further characterization of the antibody response induced in camelids, MERS-CoV-specific variable domains of heavy-chain-only antibody (VHHs) were isolated from immunized alpacas and showed potent prophylactic and therapeutic efficacies in the Ad5-hDPP4-transduced mouse model. These results highlight the inactivated rabies virus-vectored MERS-CoV vaccine as a promising camelid candidate vaccine.